Needs Analysis of an SRL-Based E-Magazine Learning Medium in Islamic Cultural History Learning at MA Annaim Ajisoko - Rindang Rabi’ah Adawiyah; Sariyatun; Akhmad Arif Musaddad Musaddad (Journal of Education and Teaching Learning, 2026)
The development of digital learning media has become increasingly important in supporting students’ active engagement and learning independence. This study aims to analyze the need for an e-magazine-based learning medium to support self-regulated learning (SRL) in Islamic Cultural History (Sejarah Kebudayaan Islam or SKI) at MA Annaim Ajisoko. A mixed-methods approach with an explanatory sequential design was employed by combining quantitative and qualitative data. The participants were 31 Grade XI students selected through saturated sampling. Data were collected using a self-regulated learning questionnaire, teacher interviews, and classroom observations. Quantitative data were analyzed descriptively using percentage scores, while qualitative data were analyzed through reduction, coding, and thematic interpretation. The findings show that students’ SRL level remains in the moderate category, with metacognition reaching 67.90%, motivation 66.20%, and behavior 65.65%. The media needs analysis indicates a high level of demand, with an overall mean of 77.90%. Observations and interviews reveal that SKI learning still relies heavily on textbooks and lecture-based instruction, limiting students’ active participation and independent learning.